PENGARUH MOTIVASI KERJA, KOMITMEN ORGANISASI, DISIPLIN KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN KOPERASI - Rasti Ardini; Fadli Fadli (UNIB Press, 2017)
This research aims to find empirically evidence that has influence of motivation, organizational commitment, discipline, and job satisfaction to employee performance. The samples of this study was 65 employees who work as financial affair of corporative in lubuk linggau. The data obtained wers analyzed by using multiple linear regression analysis. The research concludes that: motivation, organizational commitment, discipline, and job satisfaction has positive influence on the performance of the who work as financial officer.Keywords : Motivation, Organisational Commitment, Discipline, Satisfaction, and Employee Performance.